THE EFFECT OF FIVE SUPPORTING VARIABLES IN MEASURING THE EQUITY BRAND AT DISTRIBUTION BABY PRODUCTS CUSSONS - Aziz Fathoni (Universitas Pandanaran, 2015)
The objective of this research was to analyze brand equity of cussons baby products fromperspective of the customer was measured from following dimensions : attitudinal loyalty,behavioral loyalty, brand awareness, brand associations and perceived quality.Data was collected from161 respondent that meet the qualifications. From data collected,then by using descriptive statistic method, linear regression modelAnalysis shows that attitudinal loyalty, behavioral loyalty, brand awareness, brandassociations and perceived quality were significantly affecting brand equity of Cussons’sbaby products. These variables (attitudinal loyalty, behavioral loyalty, brand awareness,brand associations and perceived quality) were positively affecting the brand equity, whichmeans that increasing these variables will also increase brand equity.